Evaluation of Cryptosporidium parvum Genotyping Techniques - Sulaiman, Irshad M. (American Society for Microbiology, 1999)
We evaluated the specificity and sensitivity of 11 previously described species differentiation and genotyping PCR protocols for detection of Cryptosporidium parasites. Genomic DNA from three species of Cryptosporidium parasites (genotype 1 and genotype 2 of C. parvum, C. muris, and C. serpentis), two Eimeria species (E. neischulzi and E. papillata), and Giardia duodenalis were used to evaluate the specificity of primers. Furthermore, the sensitivity of the genotyping primers was tested by using genomic DNA isolated from known numbers of oocysts obtained from a genotype 2 C. parvum isolate. PCR amplification was repeated at least three times with all of the primer pairs. Of the 11 protocols studied, 10 amplified C. parvum genotypes 1 and 2, and the expected fragment sizes were obtained. Our results indicate that two species-differentiating protocols are not Cryptosporidium specific, as the primers used in these protocols also amplified the DNA of Eimeria species. The sensitivity studies revealed that two nested PCR-restriction fragment length polymorphism (RFLP) protocols based on the small-subunit rRNA and dihydrofolate reductase genes are more sensitive than single-round PCR or PCR-RFLP protocols.